579 Pre-operative computed tomography evaluation of suprarenal aortic burden predicts post-procedural acute kidney injury after transcatheter aortic valve replacement: the spread-AKI study. (8th December 2021) - Marzo, Vincenzo De; Seitun, Sara; Viglino, Umberto; Matos, Joao Gavina; Pigati, Maria; Vercellino, Matteo; Crimi, Gabriele; Balbi, Manrico; Porto, Italo
Abstract: Aims: Acute kidney injury (AKI) is a potential complication of transcatheter aortic valve replacement (TAVR). Athero-embolization linked to catheter manipulation in the supra-renal aorta is a possible pathogenetic mechanism of AKI after TAVR. We sought to determine the impact of supra-renal aortic atheroma burden (AB) on AKI, and the potential role of pre-operative multislice computed tomography (PO-MSCT) in evaluating the supra-renal aortic atherosclerosis and the pre-operative risk of AKI. Methods and results: We collected PO-MSCT, as well as baseline, procedural, and post-procedural characteristics of 222 consecutive patients who underwent TAVR from January 2018 to December 2020 at a single, high-volume, Italian centre. PO-MSCT was performed using a dedicated TAVR protocol with an ECG-triggered high-pitch spiral acquisition. The non-contrast aortic valve calcium score (AV-CS) was calculated by a dedicated software. Angiographic data were analysed on a dedicated 3D workstation. Bidimensional measurements, total renal volume (TRV), and presence of significant (≥50%) renal artery stenosis (RAS) were recorded. The supra-renal AB was quantified using a 'plaque analysis' module that automatically segments the entire aortic root, from the sino-tubular junction to the renal arteries, by drawing a centreline across the aortic lumen and delineating the inner and outer vessel walls (including the plaque). Manual correction was applied. A set of Hounsfield unit (HU) intensity ranges were defined and mapped to a color overlay to visualize the various elements of atherosclerotic lesion by using the plaque density classification of the Society of Cardiovascular Computed Tomography (necrotic core, fibro-fatty, fibrous, and calcified plaque); calcified plaque were subcategorized on a voxel-level basis into three strata: low- (351–700 HU), mid- (701–1000 HU), and high-calcium (>1000 HU, termed 1K plaque). Post-procedural complications were defined according to Valve Academic Research Consortium (VARC-3) criteria. Mean age was 83.3 ± 5.7 years, and 95 (42.8%) patients were males. AKI occurred in 67/222 (30.2%). Patients who developed AKI had higher supra-renal AB (17.6 ± 5.1% vs. 13.9 ± 4.3%, P < 0.001), TRV indexed for body surface area (TRVBSA ; 153.7 ± 43.1 vs. 134.9 ± 38.7, P = 0.002), mid-calcium plaque (2.2 ± 1.5% vs. 1.3 ± 1.1%, P < 0.001), 1K plaque (5.4 ± 3.7% vs. 2.4 ± 2.4%, P < 0.001) and suffered more post-procedural major/life-threatening (severe) bleedings [9/67 (13.4%) vs. 5/155 (3.2%), P = 0.004], whereas there was no difference in AV-CS ( P = 0.691) and RAS ( P = 0.077). Multivariate logistic regression analysis adjusted for other univariate predictors (male sex, baseline eGFR, baseline ejection fraction, baseline mean aortic gradient, and RAS) showed percent supra-renal AB (HR: 1.15, 95% CI: 1.06–1.26, P = 0.002), mid-to-high calcium plaque (HR: 5.67, 95% CI: 2.49–13.77, P < 0.001), severe bleedings (HR: 4.93, 95% CI: 1.09–24.69, P = 0.043), and TRVBSA (HR: 1.015, 95% CI: 1.01–1.02, P = 0.021) as independent predictors of AKI. Finally, a 3-knots spline curve analysis identified percent of supra-renal AB > 15.0% as the optimal threshold to predict an increased risk of AKI. Conclusions: Suprarenal AB is associated with the occurrence of AKI, and this association is strengthened as the percentage of calcified plaque increases. Quantitative and qualitative pre-operative MSCT assessment of aortic atherosclerosis may help in early identification of patients at high-risk for AKI who could benefit from higher peri-operative surveillance.